SERENDIPITY IN THE DIET OF THE ZAPALLAREN TREE IGUANA LIOLAEMUS ZAPALLARENSIS (MÜLLER & HELLMICH, 1933) IN VALPARAISO, CHILE - Chávez-Villavicencio, César (2022)
In Chile, texts written about reptiles usually describe the species of the genus Liolaemus as insectivorous, omnivorous and sometimes herbivorous. However, no greater level of detail is given. Within the genus Liolaemus is Liolaemus zapallarensis (Müller & Hellmich, 1933), a species endemic to Chile that inhabits coastal scrub with rocks, and is known to be omnivorous, including green shoots and flowers. In order to contribute to the knowledge of the diet of this species, the objective of this note is to report the casual record of an unknown component in the diet of the species. We report the predation and swallowing of an individual of the spider Acanthogonatus sp. by L. zapallarensis in a dune with a high degree of anthropic intervention. Hunting occurred quickly and effectively.